Comparative Analysis Of Balances Of Payments Of Ukraine And Poland In The Post-crisis Economic Environment; Analiza poroẃnawcza bilansu płatniczego w Polsce i na Ukrainie po kryzysie sŕodowiska gospodarczego - Nazariy Lypko (Comparative Economic Research. Central and Eastern Europe, 2013)
The condition of a country's balance of payments is a crucial factor for effective development in small open economies, such as Poland and Ukraine. Because of their dependence on the climate in international markets, Poland and Ukraine are especially vulnerable to fluctuations in the global situation. Thus it is essential for both national economies to develop effective instruments for adjusting their balance of payments accounts. This necessity in turn requires research into the main mechanisms used for making balance of payments adjustments for developing countries, since not all aspects have been yet explored. A comparative analysis of the balance of payments situations in these countries is conducted in this article, which aims to prove external similarities between both countries and explain why Poland has attained greater success in the process of overcoming the consequences of the global financial crisis. Such conclusions can be used as a roadmap for Ukraine on its way to adjustment of its balance of payments account. The main reason for such exploration is that Ukraine's balance of payments is still operating in deficit conditions, which negatively affects the overall state of the national economy of the country. – – Stan bilansu płatniczego kraju stanowi jeden podstawowy miernik efektywnego rozwoju w małych otwartych gospodarkach takich jak Polska I Ukraina. Z powodu ich zalezṅosći od klimatu biznesowego na rynkach miedzynarodowych, Polska i Ukraina sa szczegoĺnie wrazl̇iwe na fluktuacje majace miejsce w skali globalnej. Tak wiec dla obu gospodarek narodowych istotny jest rozwoj́ efektywnych instrumentoẃ dla dostosowania ich bilansu rachunkoẃ płatniczych. Wymaga to wiec prowadzenia badanṕodstawowych. Koniecznosćt́a wymaga z kolei prowadzenia badanṕodstawowych głoẃnych mechanizmoẃ wykorzystywanych do dokonania korekty bilansu płatniczego w krajach rozwijajacych sie, poniewazṅie wszystkie aspekty z tym zwiazane zostały juzḋotychczas dostatecznie zbadane. W niniejszym artykule została przeprowadzona analiza poroẃnawcza sytuacji bilansu płatniczego w badanych obu krajach , ktoŕa ma na celu wykazanie zewnetrznych podobienśtw miedzy nimi w tym zakresie oraz wyjasńienie, dlaczego Polska osiagneła wiekszy sukces w procesie przezwyciezȧnia skutkoẃ sẃiatowego kryzysu finansowego. Wnioski płynace z tej analizy moga stanowicŕodzaj mapy drogowej dla Ukrainy na drodze do korekty bilansu rachunkoẃ płatniczych. Głoẃnym powodem podjecia takich badanj́est obserwacja zė bilans płatniczy Ukrainy funkcjonuje w warunkach deficytu, co z kolei negatywnie wpływa na ogoĺny stan gospodarki narodowej tego kraju.
Keywords: 330; balance of payments; current account; capital account; small open economy; adjustment of balance of payments